TRADITIONAL GAMES AND THEIR CONTRIBUTION TO THE RESPECTFUL CHARACTER IN CHILDREN - Chatarina Adinda Febrianty; Gregorius Ari Nugrahanta (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
Abstract This research aims to cultivate the respect character of children aged 6-8 years through the development of traditional games manual book. The method used was the ADDIE type of R&D (Research and Development) development method. The manual book was developed through several stages, namely analyze, design, develop, implement, and evaluate stages. The research subjects involved six children (three girls and three boys) between the ages of 6-8. The research also involved seven teachers who have been certified as professional educators to conduct needs analysis and nine validators as expert judgement. The research results are shown that 1) Traditional games manual book were developed with ADDIE stages, 2) Traditional games manual book shows a quality of 3,770 (scales 1-4) included in the